2019
DOI: 10.1080/14786419.2019.1607856
|View full text |Cite
|
Sign up to set email alerts
|

One new benzophenone and one new 1,3-diphenylpropane from the fibrous roots of Anemarrhena asphodeloides Bge. and their cytotoxicity

Abstract: One new benzophenone (1) and one new 1,3-diphenylpropane (2) were obtained from the fibrous roots of Anemarrhena asphodeloides Bge. Their structures were determined by comprehensive 1D, 2D NMR and HRESIMS data. By comparing the calculated ECD curves and OR with the experimental data the absolute configurations were determined. The antitumor activity of all isolates was evaluated against two human hepatoma carcinoma cells (HepG2 and Hep3B) in vitro. The results demonstrated that compound 1 and 2 showed potent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Anemarrhenoside is a steroidal saponin monomer extracted from the dried rhizome of Anemarrhena asphodeloides , while also being its most abundant component [ 68 70 ]. Saponins E-I, E-II, B-II, B-III, and A-III of Anemarrhena asphodeloides can promote the production of SOD.…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Anemarrhenoside is a steroidal saponin monomer extracted from the dried rhizome of Anemarrhena asphodeloides , while also being its most abundant component [ 68 70 ]. Saponins E-I, E-II, B-II, B-III, and A-III of Anemarrhena asphodeloides can promote the production of SOD.…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Thus, our study proved that PFRAAB was a potential oral immune enhancer. Furthermore, the literature reported that FRAAB contains small molecules with antitumour and neuroprotective effects [ 30 ] but the effects of macromolecular substances such as polysaccharides in PFRAAB have rarely been reported. Our research provides a further understanding of FRAAB.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of evidence has revealed the potential antitumor activity of A. asphodeloides Bge. [13,14]. As the main active components of A. asphodeloides Bge., benzophenones have a broad spectrum of biological and pharmacological activities [15,16].…”
Section: Introductionmentioning
confidence: 99%